Individualized 3D-Printed Tissue Retraction Devices for Head and Neck Radiotherapy - Herpel, Christopher; Schwindling, Franz Sebastian; Held, Thomas; Christ, Leo; Lang, Kristin; Schwindling, Martha; Moratin, Julius; Zaoui, Karim; Moutsis, Tracy; Plinkert, Peter; Herfarth, Klaus; Freudlsperger, Christian; et al. (Frontiers in Oncology, 2021)
Radiotherapy for head and neck cancer may cause various oral sequelae, such as radiation-induced mucositis. To protect healthy tissue from irradiation, intraoral devices can be used. Current tissue retraction devices (TRDs) have to be either individually manufactured at considerable cost and time expenditure or they are limited in their variability. In this context, a 3D-printed, tooth-borne TRD might further facilitate clinical use. A novel approach for the manufacturing of TRDs is described and its clinical application is analysed retrospectively. The devices were virtually designed for fabrication by 3D-printing technology, enabling – in only a single printing design – caudal or bi-lateral tongue displacement, as well as stabilization of a tongue-out position. For a total of 10 patients undergoing radiotherapy of head and neck tumors, the devices were individually adapted after pre-fabrication. Technical and clinical feasibility was assessed along with patient adherence. In one exemplary case, radiotherapy treatment plans before and after tissue displacement were generated and compared. The reproducibility of maxillomandibular relation at device re-positioning was quantified by repeated intraoral optical scanning in a voluntary participant. 3D-printing was useful for the simplification of TRD manufacture, resulting in a total patient treatment time of less than 30 min. The devices were tolerated well by all tested patients over the entire radiation treatment period. No technical complications occurred with the devices. The TRDs caused an effective dose reduction in the healthy adjacent tissue, e.g. the tongue. The tooth-borne TRDs limited position changes of maxillomandibular relation to a mean value of 98.1 µm ± 29.4 µm root mean square deviation between initial reference and follow-up positions. The presented method allows a resource-efficient fabrication of individualized, tooth-bourne TRDs. A high reproducibility of maxillomandibular relation was found and the first clinical experiences underline the high potential of such devices for radiotherapy in the head and neck area.